TO THE EFFECTIVENESS OF A LEGAL MECHANISM AIMED AT INCREASING LABOUR MOBILITY - Shvaleva Elena (Электронное приложение к Российскому юридическому журналу, 2019)
The article is devoted to the legal regulation aimed at increasing territorial mobility of labour force through the regional programs. Employers taking part in these programs receive financial support from the budget of the RF subject and the federal budget in order to attract labour force. At the same time, the results of the implementation of programs from 2015 to 2018 show that it is difficult to talk about a significant increase in labour mobility. The possible reasons of such results, prospects for the development of legal regulation of these relations, and conditions of fixed-term employment contracts with attracted workers are examined.